Morphological Process of Compound Words on Food and Beverage Names in J.CO Donuts & Coffee - Fitri Rahmawati Astiandani (LITERA KULTURA : Journal of Literary and Cultural Studies, 2020)
Abstract Opting for food and beverage names on the menu list becomes a significant part of the marketing strategy. The only aim is to attract more consumers. Therefore, several culinary businesses such as restaurants, cafes, or food stall provide menu lists written in English and in a unique way either by combining words or forming a new word. In this case, morphological process plays a significant role in forming compound words. The purpose of the study is to describe the process of forming the compound words as well as classify the semantic types and meanings on food and beverage names in J.CO Donuts & Coffee. This study applies a descriptive qualitative method and theories from Delahunty and Garvey (2010) and Lieber (2009) in analyzing the data. In gaining the data analysis, several processes of analysis are done, they are (1) describing the formation of each name, (2) classifying the names based on its classes in compound category, (3) finding the meaning of each name then categorize it according to the semantic types and meaning. The result shows that food and beverage are formed from compound nouns, compound adjectives, and neo-classical compounds with three classifications namely double morpheme, double compound words, and without double morpheme and double compound. In semantic types and meanings, there are found endocentric compound with transparent meaning and exocentric compound with opaque meaning. Keywords: morphological process, compound words, endocentric and exocentric compound, transparent and opaque meaning, food and beverage names